Agronomic evaluation of Leucaena. Part 2. Productivity of the genus for forage production in subtropical Australia and humid-tropical Philippines - Mullen, BF; Gabunada Junior, FA; Shelton, HM; Stür, Werner W. (Springer, 2003)
Leucaena leucocephala is an important agroforestry species pan-tropically, but relatively little is known of the forage production potential of other species in the genus. The agronomic potential of 116 accessions, represent ing the 28 species and subspecies of the Leucaena genus and several artificial hybrid accessions, was evaluated at Los Baños, Philippines and Brisbane, Australia over a 2.5–year period. Accessions were planted into replicated line plots, with 10 trees/plot spaced 50 cm apart, and with rows spaced 3 m apart. The L. pallida × L. leuco cephala KX2 F 1 hybrid accessions were highest yielding at both sites, producing dry matter (DM) yields of over 900 g/m row/month at Los Baños and approximately 320 g/m row/month at Brisbane. In the near-optimal growth conditions at Los Baños, L. leucocephala accessions were highly productive, with the best accessions producing total yields of over 500 g/m row/month. The superiority of KX2 hybrids was most pronounced at Brisbane, where high psyllid pressure during summer, and low temperatures during winter severely constrained growth of L. leu cocephala accessions. In the Brisbane environment, psyllid resistant accessions of L. pallida , L. trichandra and L. diversifolia were more productive than L. leucocephala accessions. Leucaena greggii , L. retusa , L. cuspidata , L. confertiflora , L. pulverulenta , L. pueblana and L. involucrata were of inherently low productivity in both the Brisbane and Los Baños environments. Mortality over the experimental period was very low for most species, particularly for L. leucocephala and KX2 accessions. The KX2 F1 hybrid accessions have considerable agro nomic potential as alternatives to L. leucocephala for use in tropical agroforestry.